A CRISPR‐Cpf1‐Assisted Non‐Homologous End Joining Genome Editing System of Mycobacterium smegmatis. Issue 9 (6th August 2018) - Sun, Bingbing; Yang, Junjie; Yang, Sheng; Ye, Richard D.; Chen, Daijie; Jiang, Yu
Abstract : Mycobacterium smegmatis is an important model strain of Mycobacterium for scientific study because it is non‐pathogenic and grows rapidly. However, research is limited by the low efficiency and time‐consuming nature of existing genome editing tools. Although the Streptococcus pyogenes CRISPR‐Cas9 system is widely used in bacterial genome editing, it cannot be introduced into M. smegmatis because of its toxicity. The authors test 14 different Cas effector proteins in M. smegmatis . Cas9 (TdCas9_m) from Treponema denticola, Cas9 (NmCas9) from Neisseria meningitidis, and Corynebacterium glutamicum codon‐optimized Cpf1 (FnCpf1_cg) from Francisella tularensis do not affect cell growth. The numbers of transformant plasmids expressing TdCas9_m, NmCas9, or FnCpf1_cg, and guide RNAs (gRNA) targeting ku (MSMEG_5580), ligD (MSMEG_6301), pta (MSMEG_0783), or ackA (MSMEG_0784) decreases by about 10‐, 10‐, or 100‐fold, respectively, compared with plasmids expressing only the Cas effector proteins. Non‐homologous end joining (NHEJ) is detected only in the CRISPR‐FnCpf1_cg system. The one‐plasmid‐based, CRISPR‐FnCpf1‐assisted NHEJ system enables N iterative rounds of genome editing in 7 N  + 2 days, with an editing efficiency up to 70%; thus, this system should greatly reduce the necessary genome manipulation time for M. smegmatis . Abstract : Highly effective genetic manipulation tools will facilitate advancing understanding of the genetics of Mycobacteria . In this study, a CRISPR‐FnCpf1‐assisted NHEJ system is developed, repairing DSBs without recombinant proteins or a homologous DNA template in Mycobacterium smegmatis and shortening the editing time. This effective and fast engineering tool will have broad utility in Mycobacterium tuberculosis, which has a remarkably slow growth rate.